Analisis Strategi Berbasis Faktor Internal pada Produsen Beras Premium Berteknologi Smart Farming: Studi Kasus PT Agro Panca Unggul - Yuliana Agustina Widiarta; Tantri Yanuar Rahmat Syah; Hamdi, Edi; Sunaryanto, Ketut (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze internal factors that affect the performance of PT Agro Panca Unggul (APU), a premium rice producer based on smart farming technology in Indonesia. The methods used include evaluating the company's resources, capabilities, and operational processes with a focus on the application of advanced technologies such as precision equipment, sensors, drones, and the Internet of Things (IoT) to improve productivity and harvest quality. The production location in Boyolali was chosen because of its fertile volcanic soil conditions and abundant water availability, supporting the growth of premium quality rice. The results of the analysis show that APU's main strengths lie in the integration of smart farming technology with modern agricultural practices, a strict quality control system, strong partnerships with local farmers, and an extensive distribution network. However, the company faces several internal weaknesses such as high initial investment costs, dependence on leased land, the need for intensive training for farmers, and limited production scale. APU's competitive advantage is supported by a focus on the premium market that cares about sustainability and technological innovation, as well as strong branding. This study recommends strengthening farmer training programs, diversifying financing sources, optimizing land management, and developing digital marketing strategies to maintain the company's competitiveness and sustainability in the premium rice market.